2022
DOI: 10.3390/v14040694
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of the Epstein–Barr Virus in Autoimmune Inflammatory Rheumatic Diseases in Northern Brazil

Abstract: The present study aimed to describe the seroprevalence infection, Epstein-Barr virus (EBV) genotypes, relate the infection’s profile with the epidemiological and corticotherapy data of patients with Autoimmune inflammatory rheumatic diseases (AIRD). A cross-sectional study was carried out with 139 individuals, 92 with systemic lupus erythematosus (SLE), 27 with rheumatoid arthritis (RA) and 20 with other autoimmune diseases, who were undergoing clinical follow-up in Brazil. Serological tests for the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Several previous studies showed an increased prevalence of EBV reactivation compared to controls and an altered humoral response to EBV in lupus patients, but with a wide range of prevalence data described [ 13 , 15 , 16 , 17 , 18 , 19 , 20 ]. Similar to our findings, Franca et al and Han et al reported a prevalence of active EBV infection of 46.65% (versus 25.92% in patients with rheumatoid arthritis) and 39.66% (versus 10.53% in healthy controls), respectively [ 14 , 20 ]. However, some data suggest a prevalence of up to 78.2% of active EBV infection in lupus patients (versus 62% in controls) [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several previous studies showed an increased prevalence of EBV reactivation compared to controls and an altered humoral response to EBV in lupus patients, but with a wide range of prevalence data described [ 13 , 15 , 16 , 17 , 18 , 19 , 20 ]. Similar to our findings, Franca et al and Han et al reported a prevalence of active EBV infection of 46.65% (versus 25.92% in patients with rheumatoid arthritis) and 39.66% (versus 10.53% in healthy controls), respectively [ 14 , 20 ]. However, some data suggest a prevalence of up to 78.2% of active EBV infection in lupus patients (versus 62% in controls) [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Considering that previous data suggested an association between EBV infection and SLE phenotype presenting with cutaneous and joint involvement, a separate analysis of the relationship between baseline clinical and viral parameters and the achievement of remission and LLDAS in these subgroups of SLE patients was performed [ 13 , 14 ]. The results of univariate and multivariate regression modeling are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Cirrhosis and liver cancer account for the primary causes of death in approximately 25% of individuals with chronic HBV infection 7 . Autoimmune diseases have been closely linked to viral infections, with studies connecting Epstein−Barr virus to SLE and rheumatoid arthritis (RA) 8 . Over several decades, a multitude of studies have reported a potential association between SLE and HBV infection, with the majority of observational studies demonstrating a reduced HBV infection rate among SLE patients 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they mentioned the relationship between EBV reactivation and the autoantibody production system and the importance of molecular mimicry. França et al [3] conducted a cross-sectional study on lytic changes in EBV in rheumatic diseases in northern Brazil. As a result, it was clarified that EBV lytic changes occurred before immunosuppression by steroids in patients with systematic lupus erythematosus.…”
mentioning
confidence: 99%